Regional Growth Dynamics in Central and Eastern Europe - Vassilis Monastiriotis (London School of Economics and Political Science (LSE), European Institute, 2011)
This paper examines the regional growth process of the countries of Central and Eastern Europe since the start of their transition to market economies. It relates this to three distinctive explanations of regional growth and examines empirically their relevance in explaining the patterns of disparity and polarisation that have emerged in these countries over the last two decades. The collapse of communism and the early transition shock that followed created in many respects an experiment-like situation with a set of 'initial conditions' conducive for analysing patterns of convergence and divergence in the processes of national economic development and cross-national catch-up growth. The path to EU accession intensified the speed of these processes at the national level thus making the corresponding regional evolutions more marked. Our empirical analysis unveils a complex pattern of non-linear regional growth dynamics with convergence tendencies largely swaddled by processes of cumulative causation. Despite the process of national catch-up growth, regional evolutions are on the whole divergent, with a pattern of convergence at the middle- and lower-ends of the distribution and a slower tendency for club formation at the higher end, and thus overall an increasing trend of polarisation.
Keywords: 330